Direct measurement of free radical levels in the brain after cortical ischemia induced by photothrombosis - Mares, J; Nohejlova, K; Stopka, P; Rokyta, R (Physiological research, 2016)
Tissue ischemia is connected with the production of free radicals (FR). This study was designed to directly measure of the amount of FR in rat brains related to a photothrombotic ischemic event shortly after establishing the lesion. A model of left hemisphere photothrombosis ischemia was used in the experiment. Brains of animals from the experimental group were removed and placed in liquid N(2) for 60 min after the green laser exposure, the control group brains, exposed to the photosensitive dye Rose Bengal (RB), were placed in liquid N(2) for 80 min after RB application, naive control brains were also briefly stored in liquid N(2). Spectroscopy of electron paramagnetic (spin) resonance was used to directly measure FR (hydroxyl (OH(.)) and nitroxyl (NO(.)). Compared to naive controls, both the ischemia and RB groups had significantly higher levels of OH(.), however, there were no differences between them. Comparison of hemispheres, i.e., with and without ischemia, in the experimental group did not show any significant difference in OH(.). NO(.) were elevated in the ischemia and RB groups compare to naive controls. Higher levels of NO(.) were found in hemispheres with ischemia compared to unexposed hemispheres. Increases in OH(.) were probably associated with the action of RB itself in this model of ischemia. Increases in NO(.) were closely related to the pathogenesis of photothrombotic ischemia and could be related to the activity of nitric oxide synthases.
Keywords: Animals; Nitrogen Oxides; Disease Models, Animal; oxidy dusíku; modely nemocí na zvířatech; Cerebral Cortex; hydroxylový radikál; elektronová paramagnetická rezonance; mozková kůra; Rats, Wistar; Hydroxyl Radical; Brain Ischemia; Male; mužské pohlaví; Electron Spin Resonance Spectroscopy; ischemie mozku; zvířata; potkani Wistar